Introduction of the special edition - Villis, Paulo Cesar Mendes; Silva, Fabrício Brito (Ciência e Natura, 2022)
The Master in environment holds annually the Environment Forum of the State of Maranhão. In 2019, the third edition of the event was held with the theme: Water Resources Management in Maranhão - Potentialities and Weaknesses for a Participatory and Decentralized Management, which presented 149 scientific papers divided into two distinct areas 82 works in the area of planning and environmental quality and 67 works in the área of health and environment. Due to the importance that the event has been showing to the State and the high scientific quality of the presented works, it was considered pertinent a wider dissemination, where all the scientific community would have access to the accomplished works, hence the idea of a Special Edition in a renowned Scientific Journal. Thus, to compose the special edition of the III Forum on the Environment, 15 articles were selected, which later underwent an “ad hoc” peer review to ensure quality. The articles have varied themes and range from environmental monitoring using georeferencing technologies, going through proposals of intervention methodology for environment recovery to articles focused on the influence of anthropic and environmental factors on human health.